Hypertension Prevalence, Health Service Utilization, and Participant Satisfaction: Findings From a Pilot Randomized Controlled Trial in Aged Chinese Canadians - Ping Zou RN, PhD; Cindy-Lee Dennis PhD; Ruth Lee RN, PhD; Monica Parry NP-Adult, PhD (SAGE Publishing, 2017)
Responding to high prevalence of hypertension and patients' preference of integrating traditional Chinese medicine for blood pressure control, the Dietary Approach to Stop Hypertension With Sodium Reduction for Chinese Canadian (DASHNa-CC) intervention was newly designed as a culturally sensitive dietary educational intervention to facilitate middle-aged and senior Chinese Canadians' blood pressure control in community. The aim of this study was to report the hypertension prevalence rate according to the data from blood pressure screening events, to describe the characteristics of health service utilization among aged Chinese Canadians, and to report the evaluation of participant satisfaction to the DASHNa-CC intervention. This study was designed as a pilot randomized controlled trial with a sample size of 60. Among 618 Chinese Canadians participated in blood pressure screening events, 54.5% (n = 337) having various levels of hypertension. Across 2 months, 38 (63.3%) participants made a total of 47 visits to see their family physicians; 20 (33.3%) participants consulted their family members 224 times for lifestyle modifications and hypertension self-management. Various forms of Chinese media were frequently used as sources of health care information, and English media were rarely accessed. Participants highly satisfied with the contents, delivery approaches, and integration of traditional Chinese medicine in the intervention. Results indicated that middle-aged and senior Chinese Canadians have high hypertension prevalence and specific characteristics of health service utilization. It is important to implement interventions, which are culturally tailored, language appropriate, using proper technology and incorporating traditional Chinese medicine, in Chinese Canadian community for hypertension control.